A PNNH Pincer Ligand Allows Access to Monovalent Iron. Issue 6 (18th December 2017) - Polezhaev, Alexander V.; Liss, Cameron J.; Telser, Joshua; Chen, Chun‐Hsing; Caulton, Kenneth G.
Abstract: Reaction of the unsymmetrically armed pincer PNNH (phosphine‐pyridyl‐pyrazole) ligand with FeCl2 yielded the five‐coordinate monomer [(PNNH)FeCl2 ], the NH proton of which captures THF through the formation of a hydrogen bond. Deprotonation of this NH functionality with Li[N(SiMe3 )2 ] did not give the four‐coordinate [(PNN)FeCl], but instead retained LiCl to yield [(PNNLi)FeCl2 ], in which the lithium bridges between the pyrazolate β‐nitrogen and one of the chlorides on iron. One‐electron reduction of this compound under CO occurred with the loss of LiCl to form the square‐pyramidal monovalent iron in [(PNN)Fe(CO)2 ], which was characterized by IR, Mössbauer, and EPR spectroscopy, X‐ray diffraction, and DFT calculations. Cyclic voltammetry studies of [(PNN)Fe(CO)2 ] showed a reversible reduction wave and the reduction product was synthesized by using KC8 . The product K[(PNN)Fe(CO)2 ] contains saturated, five‐coordinate Fe 0 ; the (PNN)Fe subunit is anionic and the K + cations cluster close to the pyrazolate side of the two CO ligands. Potassium electrophile complete its coordination sphere through interactions with the oxygen atom of a CO of a neighboring unit, thereby creating a polymeric chain. The reaction of [(PNN)Fe(CO)2 ] with HBpin (4, 4, 5, 5‐tetramethyl‐1, 3, 2‐dioxaborolane) resulted in the reduction of the metal center (by release of H2 ) and borylation of the pyrazole β‐nitrogen atom. This redox‐active addition of the H−B bond across the metal–ligand assembly is an unusual example of metal–ligand cooperativity and establishes a ligand that supports iron in three different oxidation states. Abstract : Pincer complexes . The asymmetrically‐armed pincer ligand PNNH (phosphine‐pyridyl‐pyrazole) was treated with FeCl2 to yield [(PNNH)FeCl2 ]. Subsequent reaction of this complex, and analysis of the products by spectroscopic techniques, X‐ray diffraction, and DFT calculations, revealed that the ligand supports iron in three oxidation states (see figure).